Talking About Justice - Xavier, Sujith (Sri Lanka: The Struggle for Peace in the Aftermath of War, 2017)
This collection brings together a diverse array of scholars to analyse the issues and points of tension that have marked Sri Lanka’s uncertain peace.
Keywords: Sujith Xavier